Effect of Phospholipids and a Transmembrane Peptide on the Stability of the Cubic Phase of Monoolein: Implication for Protein Crystalization from a Cubic Phase - Chupin, V. (Biophysical Society, 2003)
The cubic phase of monoolein has successfully been used for crystallization of a number of membrane proteins. However, the mechanism of protein crystallization in the cubic phase is still unknown. It was hypothesized, that crystallization occurs at locally formed patches of bilayers. To get insight into the stability of the cubic phase, we investigated the effect of different phospholipids and a model transmembrane peptide on the lipid organization in mixed monoolein systems. Deuterium-labeled 1-oleoyl-rac-[(2)H(5)]-glycerol was used as a selective probe for (2)H NMR. The phase behavior of the phospholipids was followed by (31)P NMR. Upon incorporation of phosphatidylcholine, phosphatidylethanolamine, phosphatidylglycerol, or phosphatidic acid, the cubic phase of monoolein transformed into the L(α) or H(II) phase depending on the phase preference of the phospholipid and its concentration. The ability of phospholipids to destabilize the cubic phase was found to be dependent on the phospholipid packing properties. Electrostatic repulsion facilitated the cubic-to-L(α) transition. Incorporation of the transmembrane peptide KALP31 induced formation of the L(α) phase with tightly packed lipid molecules. In all cases when phase separation occurs, monoolein and phospholipid participate in both phases. The implications of these findings for protein crystallization are discussed.